Hollow nickel fiber via electrospun water soluble polymer core template - Muhammad Luqman Hakim Borhan (Nanyang Technological University, 2021)
Nanotechnology is one of the fastest growing scientific disciples due to its capabilities and high potential in producing novel materials with advanced application. With technology such as electrospinning, nanofibers can be easily produced. Since Polyvinyl alcohol (PVA) forms excellent nanofibers through electrospinning, it has attracted many industries to explore and take advantage of its potential. With its high surface area and porosity, it serves well in applications like ultrafine separation filters, biomedical equipment, absorption layers in protective clothing and many more. In this study, Polyvinyl alcohol (PVA) nanofibers will be used as filters to filter water and air from tiny particles and heavy metal ions that poses threat to public health. Since Polyvinyl alcohol (PVA) is water soluble, the objective is to create a metal hollow like structure using Polyvinyl alcohol (PVA) as the core template while the Nickel is coated on the outer layer whilst using technologies like electrospinning and electroless plating.